PENGARUH MEDIA FUN THINKER TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA DINI USIA 4-5 TAHUN DI TK PEMBINA 3 PEKANBARU - Asri, Hazimah; Novianti, Ria; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research purposed is know the effect of fun thinker through ability to recognize alphabet in 4-5 years old in Pembina 3 kindergarten Pekanbaru. As for population in this research is all of student,. sample of this research are 30 students. Method that use is experiment pretest-posttest control group design to observe there is an effect between media of Fun Thinker and student?s ability to know about alphabet. Technique of collection data is observation. Teqnique of analysis data use experiment of scale and analysis of statistical method by using spss for windows ver.24. According to result of experimental hypothesis that got, there is significant effect between media of Fun Thinker and student ability in knowing alphabet on 4-5 years old children in Pembina 3 kindergarten Pekanbaru. Criteria of experimental of hypothesis is data get improving significantly if Sig. <0,05 if Sig. > 0,05 so Ho is accepted, score of statistical experimental thitung as 7,216 and Sig. 2 tailed = 0,00 < 0,05 so we can conclude that found effect of media Fun Thinker Through student ability in knowing alphabet on 4-5 years old childrean in Pembina 3 kindergarten Pekanbaru as 57,94%Keywords: Student ability in knowing alphabet, Media Fun Thinker